STRATEGI DIVERSIFIKASI SEBAGAI TOOLS PENYELAMAT KINERJA PERUSAHAAN DI MASA PANDEMI - Sarwendhi, Rezza (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This study aims to analyze the diversification strategy has a significant impact on company performance in creating profit. The diversification strategy in question is a business growth or development strategy by developing products into several types of products or types of segments. This study also has control variables consisting of leverage and firm size. This research was conducted on manufacturing companies that were detected as carrying out a diversification strategy. The data source used comes from primary data obtained from the official website of the Indonesia Stock Exchange (IDX). The year of the research implementation is 2016-2019. This research is a predictive research that will be used to track whether a diversification strategy can be used as an effort to maintain stable company performance even during a pandemic. This research used in this study was SPSS version 26. The number of samples used in this study were 100 manufacturing companies that carried out a diversification strategy. The theory used in this study was agency theory. The test results state that the diversification strategy has an influence on company performance. Likewise with the control variable used, leverage also has an impact and influence on company performance, but for company size it has no effect on company performance.